Effect of strategic supplementation on growth performance and economics of Barbari goat kid production on rangelands - CHAUDHARY, U B; TRIPATHI, M K; TRIPATHI, PRABHAT; KUMAR, RAVINDRA (The Indian Journal of Animal Sciences, 2015)
The effect of supplementary feeding of concentrate feeds was assessed on performance, and economics of kids with grazing based production system. Male Barbari kids (30) were divided randomly in 5 equal groups. Kids were allowed 8 h daily grazing and offered arhar straw (Cajenus cajan) ad lib. after grazing for 128 days. Kids of control group did not provide any concentrate supplement, while other kid groups received either concentrate pellet feed (CPF), barley grains (BG), wheat bran plus mineral mixture and salt (WBMS) or barley grain plus mineral mixture and salt (BGMS) at 1% of live weight after grazing. The final live weights were the highest in CPF (27.6 kg) supplemented kids, whereas other groups of kids had the lower final live weights. Total live weight gains were higher in CPF (12.33 kg), BG (10.20 kg) and BGMS (10.03 kg) supplemented kids in comparison of control (7.18 kg) and WBMS (9.05 kg) group of kids. Average daily gain (ADG) ranged between 51.6 and 88.7 g, which is higher in the kids of CPF group. The CPF supplementation improved growth of kids by 73%, followed by BG (42%) than that occurred in control kids. Total volatile fatty acids and NH3-N were similar among the groups, whereas concentrate supplemented kids had the higher protozoa population in rumen fluid. Hematology and plasma minerals were also not different among kids groups. Although the supplementary feeding have increased the cost of feeding from Rupees 227 to 401 on each kid, however net return on each kid over the control wereÂ Rupees 467, 712, 755 and 1,287, respectively, in WBMS, BGMB, BG and CPF group of kids. Study concluded that supplementary feeding of 1.0% concentrate provided higher economic returns over the kids managed on grazing alone, and the feeding of concentrate pellet provided maximum net returns.